A case study on the relationship of education policy and practice in regard to migration - Marouli, Maria-Nefeli (2024)
Literature suggests that students with migrant backgrounds are exposed to vulnerable positions in education. Finland is a country with a rising migrant rate. Thus, this study focuses on exploring the relationship between education policies and grassroot level practices regarding migrant students on a school at a municipal setting in Central Finland.